Magnetic Frequency Tuning of a Shape Memory Alloy Thermoelectric Vibration Energy Harvester - Ivo Yotov; Georgi Todorov; Todor Gavrilov; Todor Todorov (Energies)
This study examines how the frequency of an innovative energy harvester is tuned and how it behaves. This harvester transforms thermal energy into mechanical oscillations of two polyvinylidene fluoride (PVDF) piezoelectric beams, which produce electrical energy via a shape memory alloy (SMA) thread. The oscillation frequency is modified by two magnetic weights that are positioned symmetrically on the SMA thread and interact with stationary NdFeB permanent magnets. The SMA thread shifts laterally due to longitudinal thermal contraction and expansion induced by a constant-temperature heater. Temperature gradients above the heater trigger cyclical variations in the length of the SMA thread, leading to autonomous vibrations of the masses in both the vertical and horizontal planes. An experimental apparatus was constructed to analyze the harvester by tracking the motions of the masses and the voltages produced by the piezoelectric beams. Information was gathered regarding the correlation between output voltage and power with the consumer’s load resistance. These outcomes were confirmed using a multiphysics dynamic simulation that incorporated the interconnections among mechanical, thermal, magnetic, and electrical systems. The findings indicate that the use of permanent magnets increases the bending vibration frequency from 8.3 Hz to 9.2 Hz. For a heater maintained at 70 °C, this boosts the output power from 1.9 µW to 8.18 µW. A notable property of the considered energy harvester configuration is its ability to operate at cryogenic temperatures.